Measuring Economic Competence of Youth with a Short Scale - Luis Oberrauch; Tim Kaiser; Günther Seeber (ZBW - Leibniz Information Centre for Economics, 2022)
We present a 12-item scale measuring the cognitive component of economic competence and document the psychometric properties of the scale. Using a data set with more than 12,000 secondary school students in Germany, the scale shows high discriminatory power and covers a wide range of ability levels. Analyses of `Differential Item Functioning show no item bias across key demographic characteristics, and scores show meaningful associations with scores obtained from adjacent test instruments. Student-level correlates mirror estimates documented in earlier literature on economic and financial literacy as well as results relying on a more extensive scale with over 30 items. The presented short scale enables researchers and practitioners to efficiently measure economic competence of youth.
Keywords: A21; I21; G53; 330; economic competence; economic literacy; IRT; measurement